Sensor Layout Design for Structural Health Monitoring - Kyung, JungHyun; An, Jae-Hyoung; Eun, Hee-Chang (Civil Engineering Journal, 2024)
This study investigates the enhancement of optimal sensor placement (OSP) algorithms by incorporating modal reduction constraints and developing combined techniques. The primary goal is to optimize sensor placement for structural health monitoring (SHM), thereby improving the efficiency of information acquisition within practical constraints. The proposed methodology utilizes iterative elimination and combined criteria to evaluate various sensor configurations. Numerical experiments demonstrate distinct sensor layouts derived from diverse algorithmic approaches. The study's novel contributions include the integration of modal strain energy, effective independence (EI), and modal assurance criterion (MAC) techniques into a unified framework, enhancing adaptability to a wide range of SHM scenarios. Doi: 10.28991/CEJ-2024-010-12-011 Full Text: PDF